2022
DOI: 10.1002/advs.202206150
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte‐Inspired Functional Materials for Biomedical Applications

Abstract: Erythrocytes are the most abundant cells in the blood. As the results of long‐term natural selection, their specific biconcave discoid morphology and cellular composition are responsible for gaining excellent biological performance. Inspired by the intrinsic features of erythrocytes, various artificial biomaterials emerge and find broad prospects in biomedical applications such as therapeutic delivery, bioimaging, and tissue engineering. Here, a comprehensive review from the fabrication to the applications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 239 publications
0
4
0
Order By: Relevance
“…4 ). More examples of RBC mimics can be found in review 50 , however, little in vivo applications have been reported to date.
Fig.
…”
Section: Rbcs As Biomimetic Systemsmentioning
confidence: 99%
“…4 ). More examples of RBC mimics can be found in review 50 , however, little in vivo applications have been reported to date.
Fig.
…”
Section: Rbcs As Biomimetic Systemsmentioning
confidence: 99%
“…[15] Fulfilling their multiple roles in blood, these cells circulate for ≈120 days before natural removal due to biological aging. [16] Erythrocytes are enucleated, biconcave-shaped cells, with a diameter range of 7.5 to 8.7 μm and thickness range of 1.7 to 2.2 μm (Figure 1A). [17] Their shape is determined by a lipid-rich cell membrane containing phospholipids and cholesterol, alternated with membrane proteins such as glycophorins, Na 2+ and K + -dependent adenosine triphosphatases, band 3 anion (Cl − and HCO 3 -) transporter proteins, ankyrin, and others.…”
Section: Structure and Function Of Erythrocytesmentioning
confidence: 99%
“…As a result of long-term natural selection, their unique biconcave disc-like morphology and cellular composition have enabled them to acquire excellent biological properties. Researchers have produced a variety of nanoparticles that mimic erythrocytes, which have been widely used in biomedical fields such as drug delivery, bioimaging, and tissue engineering [19].…”
Section: Introductionmentioning
confidence: 99%